Observing phubbing behaviors during casual and serious conversations: consequences for conversation quality, connectedness, and appropriateness - Anja Stevic; Hanna Liftinger; Jörg Matthes (BMC Psychology)
Abstract The present study investigated observers’ perspectives of smartphone use during social interactions in serious and casual conversational contexts, suggesting gender differences. The results of the between-subjects 2 × 2 experimental study show that female observers perceive lower conversation quality when observing phubbing than male observers, aligning with the need-threat model’s assertion of female susceptibility to social exclusion. Moreover, observing phubbing diminishes perceived appropriateness of the interaction. Interestingly, no disparity was found in casual versus serious topics of the conversations. Societal implications are discussed.